Solar–biogas microgrid: a strategy for the sustainable development of rural communities in Pakistan - Faisal Nawab; Ag Sufiyan Abd Hamid; Muhammad Arif; Tufial A. Khan; Amir Naveed; Muhammad Sadiq; Sahibzada Imad Ud din; Adnan Ibrahim (MDPI, 2022)
Access to uninterrupted power is not a luxury but a basic need. Rural communities living far from the national grid, particularly those in the southern region of Pakistan’s Khyber Pakhtunkhwa province, have limited access to a reliable power supply. In order to provide sustainable electricity, small-scale off-grid renewable energy systems are increasingly used for rural electrification. These systems are commonly known as stand-alone home systems or community micro-grids. This paper proposes an off-grid solar–biogas micro-grid for rural communities in the Lakki Marwat district of Khyber Pakhtunkhwa, Pakistan. The area is mainly dependent upon income from the agricultural and livestock sectors. HOMER was used to simulate the electric power system, while RET-Screen was used to analyze the economics of the system. The optimized system’s results demonstrate that the most economically and technically possible system, which produces 515 kWh and 338.50 m3 biogas daily, is made up of a 30-kW photovoltaic system coupled with a 37-kW biomass hybrid system, a 64-kWh battery storage capacity, and a 20-kW invertor. The system will meet the cooking and power needs of 900 individuals who reside in 100 homes. In addition to household users, the system will provide fixed-priced electricity to productive buildings, and free electricity to community buildings. The system will generate 1300 kg of organic fertilizer each day, which will be sold to local farmers for 50% less than what it would cost on the open market. The proposed approach is techno-economically viable based on the payback period and internal rate of return.